1985
DOI: 10.1111/j.1532-5415.1985.tb02855.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Functional Correlates of Low Back Pain in the Elderly: The Iowa 65+ Rural Health Study

Abstract: As part of an interview survey of a defined population of 3,097 rural persons 65 years and older (the Iowa 65 + Rural Health Study), the prevalence and functional correlates of specifically defined low back pain were studied. Low back pain was reported by 23.6 per cent of the women and 18.4 per cent of the men in the year prior to the survey, with prevalence rates declining with age. Forty per cent of those with low back pain noted its presence at the time of the interview. Over half had used analgesics. Use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
95
1
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 9 publications
4
95
1
4
Order By: Relevance
“…Fanuele et al found that the impact of spinal problems on physical functional status was similar to the impact of conditions like congestive heart failure or to functional status prior to primary total hip arthroplasty or prior to primary total knee arthroplasty in a population-based sample of more than 17,000 people aged 17-98 years [10]. In the older population, both Leveille et al and Lavsky-Shulan et al, in population-based studies, found that the presence of BP significantly influenced physical functional abilities of older people [24,27]. The question, of course, remains whether these limitations in physical functioning are caused by BP as an isolated symptom, or whether they are due to a combined effect of several health problems, one of which is BP.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Fanuele et al found that the impact of spinal problems on physical functional status was similar to the impact of conditions like congestive heart failure or to functional status prior to primary total hip arthroplasty or prior to primary total knee arthroplasty in a population-based sample of more than 17,000 people aged 17-98 years [10]. In the older population, both Leveille et al and Lavsky-Shulan et al, in population-based studies, found that the presence of BP significantly influenced physical functional abilities of older people [24,27]. The question, of course, remains whether these limitations in physical functioning are caused by BP as an isolated symptom, or whether they are due to a combined effect of several health problems, one of which is BP.…”
Section: Discussionmentioning
confidence: 56%
“…A population-based study of 4486 Danish twins aged 70-102 mated for old versus very old persons (i.e. 75-80-vs 81-85-year-olds), but results have been conflicting, ranging from a higher prevalence in oldest age groups [7,17] over no difference [9], to a decreased prevalence with increasing age [1,16,24]. In none of these studies, however, were identical, repeated measurements performed in the same cohort, and the actual development of BP over time late in life has yet to be established.…”
mentioning
confidence: 99%
“…[24] [79] [108] Because pain is often remediable, [2] [25] it is thought that the high prevalence estimates of unrelieved pain in elderly persons may result from underrecognition, which in turn results in undertreatment. [65] [91] [120] The consequences of untreated pain can profoundly impact the older person's quality of life.…”
Section: Prevalence and Consequences Of Pain In Older Adultsmentioning
confidence: 99%
“…This is surprising because populationbased figures indicate that the prevalence of pain is twofold higher in those over age 60 (250 per thousand), compared with those under age 60 (125 per thousand). [24] [79] [108] Further, prevalence estimates suggest that approximately 60% of community-dwelling older adults and up to 80% of elderly long-term care facility residents experience substantial pain.[24] [79] [108] Because pain is often remediable, [2] [25] it is thought that the high prevalence estimates of unrelieved pain in elderly persons may result from underrecognition, which in turn results in undertreatment. [65] [91] [120] The consequences of untreated pain can profoundly impact the older person's quality of life.…”
mentioning
confidence: 99%
“…In a survey comprising 3,000 Americans age 65 years and older, one-fifth reported experiencing low back pain [13]. This pain interferes with activities of daily living, sleep, quality of life, etc.…”
mentioning
confidence: 99%